Analisis Strategi Algoritma Sorting Menggunakan Metode Komparatif pada Bahasa Pemrograman Java dengan Python - Joko Iskandar; Heri Suhendar; Bian Dwi Pamungkas (G-Tech: Jurnal Teknologi Terapan, 2024)
Applying the right sorting algorithm strategy is a key factor that cannot be underestimated, especially for system developers. This research aims to comprehensively analyze six sorting algorithm strategies using two programming languages, Java and Python. The sorting algorithm strategies include bubble, selection, insertion, shell, merge and quick sort. The data analysis ranged from 1000 data to 200,000 data. The results showed that the sort algorithm strategies for bubble, selection and insertion at more than 20,000 data were faster using Java than Python, while the shell, merge and quick sort strategies after more than 20,000 resulted in execution times that were not much different using both Java and Python programming languages.